Identify, Analyze and Categorize the Factors Affecting Sharing Web Knowledge in Libraries Using the Fuzzy Delphi Approach - Taherkhani, Leyli; Limooni, Safiyeh Tahmasebi; Ghiasi, Mitra (International journal of information science and management, 2022)
Web knowledge sharing is a developmental approach for content production systems in the Internet space that can reduce the cost of information dissemination and increase the efficiency of systems, so the purpose of this study is to identify, analyze and categorize the factors affecting Sharing web knowledge in libraries is a fuzzy Delphi approach. : This research is exploratory in terms of purpose, fundamental in terms of research audience, and qualitative in terms of the type of research. The statistical population of the study consisted of 15 experts including the professors of the Knowledge and Information Science department, professors of information technology management, and the managers of libraries who were fully acquainted with the subject of web knowledge sharing .These subjects were selected by snowball sampling method to reach theoretical saturation. The data collection instrument is semi-structured interviews. The six stages of thematic analysis were used to identify the factors affecting the knowledge web sharing the Fuzzy Delphi technique was applied for the consensus opinions of experts. The resulting data were analyzed using PSS24 and PLS3.8 software. The results obtained from Delphi-fuzzy theme analysis and technique indicated that the main factors of web knowledge sharing in libraries of Iran include three main factors, "desirability of web information" with three components (trust and reliability, perception and usefulness), "Web space desirability" with four components (ease of use, accessibility, usability, and security) and "people desirability" with two components (internal and external motivations) were identified. It was found that the web space desirability factor with a coefficient of the impact of 0.917 had the most impact and was the priority and factor of web information desirability with a coefficient of 0.858; and the desirability of individuals with a coefficient of 0.813 was in the second and third priorities of the impact factor, respectively. According to the opinion of experts, web knowledge sharing as a flexible capability to deliver content aims to provide quick access to knowledge on the web and integrate it into the library. Consequently, it is necessary for the libraries to constantly identify the production, exchange, and application of knowledge among their employees to find ways to achieve organizational goals.